Cash Waqf-Based Crowdfunding Model Using Blockchain Technology: Problem, Solution, and Strategies for Family Waqf - Matla'il Fajar, Abbas Sofwan; Syamsuri; Dwi Karunia Arti; Vina Fithriana Wibisono (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
The development of waqf nowadays has utilized technology to using crowdfunding platforms as an effort to increase waqf acceptance. In the other hand, the effect of crowdfunding become of information technology is proportional to the level of risk posed. It obstacles faced in implementation of sharia securities crowdfunding are in terms of legality and security and create loopholes for committing crimes legal problems. Therefore, using blockchain in waqf crowdfunding can be a solution to overcome security and transparency risks in crowdfunding and record transactions rights to funded projects in a transparent and verified manner. The purpose of this study is to create best solutions and strategies in solving problem of crowdfunding platform in cash waqf. This study uses a qualitative approach with Analytic Network Process (ANP) method through in-depth interview approach, focus group discussion and filling out questionnaires to regulators, practitioners, and academicians related to a problem. The result of this study found best strategy offered to overcome the problems of cash waqf crowdfunding platform is increasing the security and transparency on the platform by blockchain technology; literacy and religiosity of Indonesian society and optimizing regulations and supervisions both in term of law and sharia.